2012
DOI: 10.1080/00330124.2011.609778
|View full text |Cite
|
Sign up to set email alerts
|

Did GIS Start a Crime Wave? SatNav Theft and Its Implications for Geo-Information Engineering

Abstract: In-car satellite navigation systems (SatNavs) are among the first products based on geographic information systems to have widespread fashionable appeal. In the United Kingdom, portable versions that are easily installed on the dashboard or front windshield have become a popular vehicle accessory. As prices have fallen, demand has increased over the last few years to the point that SatNavs might soon achieve the ubiquity of in-car entertainment systems. The rise of popularity of SatNavs, however, has also brou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…With regard to victimization, the routine activity approach directly refers to suitable targets. In fact, one of the primary interests of Cohen and Felson (1979) are the increases in target suitability in the post-1950s era, particularly in the development of (relatively) lightweight electronics that continues to impact crime patterns today (Mailley et al, 2008;Whitehead and Farrell, 2008;Brimicombe, 2012). However, in their empirical assessment, Cohen and Felson (1979) found that changes in routine activities were the drivers of increases in crime patterns.…”
Section: Crimrxivmentioning
confidence: 99%
“…With regard to victimization, the routine activity approach directly refers to suitable targets. In fact, one of the primary interests of Cohen and Felson (1979) are the increases in target suitability in the post-1950s era, particularly in the development of (relatively) lightweight electronics that continues to impact crime patterns today (Mailley et al, 2008;Whitehead and Farrell, 2008;Brimicombe, 2012). However, in their empirical assessment, Cohen and Felson (1979) found that changes in routine activities were the drivers of increases in crime patterns.…”
Section: Crimrxivmentioning
confidence: 99%
“…The town has a large enough college presence to show marked increases when students come to and leave town. A problem crime is frequently thefts of small electronics from motor vehicles (Brimicombe, 2012), with a large proportion being from unlocked vehicles. Increases in thefts from motor vehicles throughout 2012 brought increased attention to community groups and the media, and the thefts precipitously decreased to 10-year lows beginning in 2013 after one prolific offender was apprehended, who later admitted to around 40 thefts in the prior 2 months.…”
Section: Time Series Charts For Monitoring Crime Seriesmentioning
confidence: 99%
“…In general, the objective of research using police-recorded data is not to focus on specific individuals per se but to identify aggregate patterns that provide new understanding and suggest interventions or solutions to problems. Two different documented examples of this type of approach are: a) an analysis of the upsurge in SatNav theft from the beginning of 2006 given in Brimicombe (2012), and b) an analysis of offender histories of those arrested in the London riots of 2011 given in Stanko and Dawson (2012).…”
Section: Advantages Of Police-recorded Datamentioning
confidence: 99%
“…a violent altercation outside a pub) or, say, at a road junction. This forms the basis of 'hotspot' mapping allowing police to focus their resources on those locations that have highest intensities of crime (Harries, 1999;Brimicombe, 2012). The data on victims and perpetrators can be further filtered by gender, age, ethnicity and offence/incident category in order to study specific patterns of activity.…”
Section: Advantages Of Police-recorded Datamentioning
confidence: 99%